The Influence of the Realistic Nalaria Mathematics Method on the Mathematics Learning Outcomes of Grade 3 Students of Bosowa Bina Insani Elementary School - Amran, Amran; Shaliha, Gita Putri Amalia; Hakim, Nurman (Jurnal Evaluasi dan Pembelajaran, 2025)
This study aims to determine the effect of the application of Mathematics Nalaria Realistic (MNR) method on the mathematics learning outcomes of 3rd grade students of SD Bosowa Bina Insani. This study used a quantitative approach with a quasi-experimental method involving two class groups, namely the control class and the experimental class. The design of this research is pretest-posttest control group design. The sample used was 46 students, consisting of 23 students of class 3A as the control class, and 23 students of class 3C as the experimental class. Data collection in this study used a test instrument consisting of 12 HOTS description questions and documentation studies. The results in the study obtained through the t test using the independent sample t test formula are that there is a significant influence between the application of the MNR method on the mathematics learning outcomes of grade 3 students, especially on fraction material with the results of tcount < ttable with 2-tailed sig results of 0.000 < 0.05 so that Ha is accepted and H0 is rejected.